Terahertz Imaging for Biomedical Applications Pattern Recognition and Tomographic Reconstruction - Yin, Xiaoxia; Ng, Brian W.-H.; Abbott, Derek; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Terahertz Imaging for Biomedical Applications: Pattern Recognition and Tomographic Reconstruction presents the necessary algorithms needed to assist screening, diagnosis, and treatment, and these algorithms will play a critical role in the accurate detection of abnormalities present in biomedical imaging. Terahertz biomedical imaging has become an area of interest due to its ability to simultaneously acquire both image and spectral information. Terahertz imaging systems are being commercialized with an increasing number of trials performed in a biomedical setting. Terahertz tomographic imaging and detection technology contributes to the ability to identify opaque objects with clear boundaries,and would be useful to both in vivo and ex vivo environments. This book also: Introduces terahertz radiation techniques and provides a number of topical examples of signal and image processing, as well as machine learning Presents the most recent developments in an emerging field, terahertz radiation Utilizes new methods of digital imaging that would be useful in medical screening, diagnosis, and treatment Terahertz Imaging for Biomedical Applications: Pattern Recognition and Tomographic Reconstruction is a must-read for anyone in the field of biomedical engineering and digital imaging.
Introduction and Motivation to Terahertz Radiation -- Terahertz Sources and Detectors -- Terahertz Imaging Modes -- Terahertz Imaging Analysis -- Pattern Formation and Recognition Using T-rays -- Wavelet Transforms -- Feature Extraction and Selection -- Pattern Classification -- THz Pattern Recognition Experiments -- Terahertz Computed Tomography -- 2D Wavelet Segmentation in 3D T-ray CT -- Wavelet-Based Terahertz Coherent Local Tomography -- Local CT Using a THz QCL -- Conclusions and Outlook.
Keywords: Engineering; Pattern recognition; Biomedical engineering; Engineering; Signal, Image and Speech Processing; Biomedical Engineering; Pattern Recognition; Electronic books